IMPLEMENTASI DIMENSI BANKING SERVICE QUALITY DAN PENGARUHNYA TERHADAP KEPUASAN DAN LOYALITAS NASABAH BANK - Hesty Budiwati; Kasno Kasno (RELASI : JURNAL EKONOMI, 2015)
This research aims to find out how the implementation dimensions of Banking Service Quality  influence directly and indirectly, as well as partially and simultaneous to the bank’s customer loyalty where customer’s satisfaction is the intervening variables. The research of measuring service quality by using dimensions of Banking Service Quality (BSQ) due to use of BSQ in some previous research has proved valid and better than SERVQUAL. BSQ dimensions developed by Bahia and Nantel to comprise effectiveness and assurance, acces,price, tangible, service portofolio, and reliability.Population research includes customer at PT BPR Sentral Arta Asia Lumajang with 120 samples. Data analysis techniques using path analysis model to do testing first substructure and second substructure. Hypothesis testing by directly and indirectly. The result showed that simultaneously influential BSQ dimensions significantly to customer loyalty, it’s influence through the variable satisfaction demonstrates the influence that strengthened the customer will increasingly loyal if BSQ dimensions is apllied to give satisfaction for the customer. Not all variables are partially significant impact, effectiveness and assurance,price, and service portofolio. While access, tangible, and reliability do not affect the customer’s loyalty.Multiple correlation coefficient values obtained of 0.553 the significance of 0.000 which means there are proven relationships whith the strong criteria positive and highly significant. While the value of the coefficient of determination of 0.306 or 30.6% means the variable dimensions BSQ able to explain it’s influence on change of variables simultaneously loyalty of 30.6% and the rest 69.4% explained by other variable.